The Effect of Liquidity, Profitability, and Firm Size on Financial Distress (In Retail Sector Companies Listed on the Indonesia Stock Exchange during the 2021-2024 Period) - Fitriyatul Arifah; Ali Muhdor (Universitas Bhayangkara Surabaya, 2026)
This study aims to analyze the effect of liquidity, profitability, and firm size on financial distress in retail sector companies listed on the Indonesia Stock Exchange during the 2021-2024 period. Financial distress is proxied by the Altman Z-Score, liquidity is measured using the Current Ratio, profitability with Return on Assets, and firm size with the natural logarithm of total assets. This research employs a quantitative approach with multiple linear regression analysis on 36 observations obtained through purposive sampling. The results show that partially, liquidity has a positive and significant effect on financial distress, while profitability and firm size have no significant effect. Simultaneously, the three variables have a significant effect on financial distress, with liquidity being the most dominant variable. These findings indicate that liquidity management is a key factor in maintaining the financial stability of retail companies.